Phylogenetic Analyses of Some Melanoleuca Species (Agaricales, Tricholomataceae) in Northern China, With Descriptions of Two New Species and the Identification of Seven Species as a First Record - Xu, Jize; Yu, Xiaodong; Lu, Mengzhao; Hu, Jiajun; Moodley, Odeshnee; Zhang, Chunlan; Gong, Lei; Li, Yu (Frontiers in Microbiology, 2019)
Two new species (Melanoleuca galerinaspora and Melanoleuca subgrammopodia) and seven new recorded species from northern China are described here using morphological and molecular methods. Melanoleuca galerinaspora is mainly characterized by its hygrophanous pileus, decurrent lamellae, fibrous stipe and spores with round warts. Key characteristics of M. subgrammopodia include its discolored pileus, fibrous stipe and urticiform cystidia. The divergence time of Melanoleuca fungi as well as the phylogenetic relationships within this genus were analyzed using DNA sequences of the internal transcribed spacer (ITS) and the nuclear large subunit rDNA (nrLSU) gene fragments. Analyses revealed that morphological identifications and phylogenetic relationships were consistent with the results of divergence time, thereby confirming that M. galerinaspora and M. subgrammopodia are new species.